PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVA SD NEGERI 55 KESUMBO AMPAI - Yusrini, Elvi; Syahrilfuddin, Syahrilfuddin; Hamizi, Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the result of lower-grade students learn math IVA SDN 55 Kesumbo Ampai, seen from the average value of the class 66.23. Therefore, the researchers provide an alternative to the implementation of cooperative learning model learning NHT in the class IVA SD Negeri 55 Kesumbo Ampai. This research aims to improve learning outcomes Mathematics IVA grade students of SD Negeri 55 Kesumbo Ampai Saber with cooperative learning model Application NHT. This research is a form of classroom action research (PTK) with 2 cycles. Based on the analysis of research data after applying cooperative learning model NHT, the average percentage of the activity of teachers in the first cycle increased by 66.66% to 85.4% in the second cycle. The average percentage of student activity also increased, namely 56.25% in the first cycle increased to 87.49% in the second cycle. Student learning outcomes in basic score with an average value of 66.23 with 46.15% and the percentage of completion in the first cycle increased with an average value of 72.11 by the percentage increase in class learning outcomes by 8.87% and the percentage of students who 73 , 07% complete. Then the average value silus class II increased to 77.60 with the percentage increase learning outcomes by 17.16% and the percentage of students who completed was 84.61%, after the implementation of cooperative learning model NHT. These results indicate that the application of cooperative learning model NHT could improve student learning outcomes Math class IVA SDN 55 Kesumbo Ampai.Keywords: Learning Model NHT, Mathematics Learning Outcomes